The role of heparan sulfate deficiency in autistic phenotype: potential involvement of Slit/Robo/srGAPs-mediated dendritic spine formation. Issue 1 (December 2016) - Pérez, Christine; Sawmiller, Darrell; Tan, Jun
Abstract Autism Spectrum Disorders (ASD) are the second most common developmental cause of disability in the United States. ASDs are accompanied with substantial economic and emotional cost. The brains of ASD patients have marked structural abnormalities, in the form of increased dendritic spines and decreased long distance connections. These structural differences may be due to deficiencies in Heparin Sulfate (HS), a proteoglycan involved in a variety of neurodevelopmental processes. Of particular interest is its role in the Slit/Robo pathway. The Slit/Robo pathway is known to be involved in the regulation of axonal guidance and dendritic spine formation. HS mediates the Slit/Robo interaction; without its presence Slit's repulsive activity is abrogated. Slit/Robo regulates dendritic spine formation through its interaction with srGAPs (slit-robo GTPase Activating Proteins), which leads to downstream signaling, actin cytoskeleton depolymerization and dendritic spine collapse. Through interference with this pathway, HS deficiency can lead to excess spine formation.